From the Tsar-Bomba to Start-I: The evolution of the Soviet strategic nuclear deterrent, 1945-1991 - Muraviev, Alexey (2025)
This chapter examines the development of the Soviet strategic nuclear deterrent over the post-1945 period, paying attention to all three elements of the Soviet Nuclear Triad. For Soviet military leaders, the introduction of nuclear weapons and other 'weapons of mass destruction' constituted a 'Revolution in Military Affairs' (RMA). Evolutionary phases of the RMA were influenced by the progressive development of the national nuclear deterrent as well as Soviet assessments of the US intent to operationalise the nuclear factor in various warfighting scenarios. Ultimately the Soviet Union would develop a nuclear weapons 'triad' similar to that of the United States, in which the Soviet emphasis was on intercontinental ballistic missiles and submarine-launched ballistic missiles. Certainly, by the mid-1980s, the Soviet Union had achieved nuclear parity with its rivals, despite the threat that the US Strategic Defense Initiative (SDI) and cruise missile development might destabilise any nuclear 'balance'.